Factors associated with the practice of clean and healthy living behavior among households in Ranombupulu Village - Siti Rabbani Karimuna; Waode Mitha Fatrisya; Irma Yunawati; Sri Tungga Dewi (Indonesian Journal of Health Science, 2026)
Clean and Healthy Living Behavior (PHBS) is an essential preventive health strategy to improve community well-being; however, its implementation remains suboptimal in several rural areas. This study aimed to describe the implementation of PHBS and analyze the relationship between knowledge, education level, income, and age with household PHBS status in Ranombupulu Village. A descriptive analytic design with a cross-sectional approach was used, involving 81 respondents selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using the Chi-square test. The results showed that only 45.7% of households properly implemented PHBS. Statistical analysis revealed no significant relationship between PHBS status and knowledge (p=0.952), education level (p=0.990), income (p=0.781), or age (p=0.890). The study concludes that PHBS implementation remains low and is not influenced by sociodemographic characteristics. Continuous health education and improved community support and facilities are recommended to strengthen PHBS adoption.